What Is the Role of AI in Surgical Decision Making? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Artificial intelligence (AI) is a transformative force in healthcare, and its integration into surgical practice holds immense promise. By leveraging machine...
Keywords: AI in Clinical Decision Support; Surgical; Decision; Making; Artificial Intelligence; Machine Learning; Healthcare